(untitled) (International Seven Journal of Multidisciplinary, 2020)
Paramedical micropigmentation has been consolidated as a relevant resource in the aesthetic and emotional rehabilitation of women undergoing mastectomy, acting as a complementary step to the breast reconstruction process and contributing to the restoration of self-esteem and body self-perception. This study analyzed Brazilian scientific publications that address the role of micropigmentation in the multidisciplinary context, evidencing the importance of its integration with other health professionals to obtain aesthetically satisfactory and psychologically significant results. Benefits related to visual naturalness, reduction of emotional impacts, and improvement in quality of life were observed, with emphasis on the need for continuous training and adoption of biosafety protocols. The findings reinforce that the qualified performance of the micropigmentation artist enhances the positive effects of the treatment, consolidating paramedical micropigmentation as an effective tool in post-mastectomy rehabilitation.